2005
DOI: 10.1177/1043659604271239
|View full text |Cite
|
Sign up to set email alerts
|

Manifestation, Attribution, and Coping With Depression Among Asian Indians From the Perspectives of Health Care Practitioners

Abstract: The study explores cultural influences on depression and care outcomes among Asian Indians with depression. Data were collected from interviews of 23 multidisciplinary mental health professionals and retrospective review of 20 medical records of patients. Findings revealed a major influence of social and cultural context in expression of symptoms, illness attribution, help-seeking behaviors, and communication patterns. Religious beliefs and social stigma attached to mental illness contributed to prolonged deni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 22 publications
3
58
0
Order By: Relevance
“…This further emphasises the fact that this group mostly complains in somatic terms. For instance, expressing mental distress in any form of pain is quite common among this group (Conrad and Pacquiao 2005) or terms like 'sinking heart' are commonly used (Krause 1989). Wilson and MacCarthy (1994) found that even when psychological complaints are made, the majority of times South Asian patients will receive physical rather than a psychological diagnosis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This further emphasises the fact that this group mostly complains in somatic terms. For instance, expressing mental distress in any form of pain is quite common among this group (Conrad and Pacquiao 2005) or terms like 'sinking heart' are commonly used (Krause 1989). Wilson and MacCarthy (1994) found that even when psychological complaints are made, the majority of times South Asian patients will receive physical rather than a psychological diagnosis.…”
Section: Discussionmentioning
confidence: 98%
“…As a result, support is often sought from the extended family, which frequently leads to the use of traditional forms of treatment, such as prayers, rituals, faith healing, and folk remedies (Chandarana and Pellizzari 2001;Dein and Sembhi 2001). In South Asian culture, mental illness is not only confined to the individual that is affected, it also brings shame and dishonour to the entire family (Chandarana and Pellizzari 2001;Conrad and Pacquiao 2005). This factor plays a significant role because of the system of arranged marriage (Chandarana and Pellizzari 2001;Qurashi 1988).…”
Section: Mental Health Depression and South Asiansmentioning
confidence: 98%
“…Physical and mental deficits are thought to be God's will or past karma. These factors may add to the delay in seeking professional help (Tavkar et al, 2008;Conrad and Pacquiao, 2005). While the above factors may influence the development of certain psychiatric disorders, one could argue that this collectivism and belief in moral and religious principles might also protect the South Asian patient from the sequelae of severe mental illness, namely suicide.…”
Section: Introductionmentioning
confidence: 98%
“…religious, supernatural) while MEMQ explains both personalistic and naturalistic causes (situations, psychobiological). Indians attribute more of a personalistic cause such as God's will, supernatural force and astrological cause for suffering or problems 28 . Prevalent astrological beliefs such as Shani (Saturn), Rahu (the ascending node of the moon) and Ketu (descending node of the Moon) is often believed to determine good or bad happening in daily life.…”
Section: Level Of Paranormal Beliefmentioning
confidence: 99%